Ideal velvet bean seed processing for human consumption - Katera Claude, Issa; Ntamwira, Jules; Blomme, Guy; Kitumaini, Nancy Safari; Shabani, Gabriel; Ocimati, Walter (2025)
Velvet bean (Mucuna pruriens), in addition to improving soil health, holds great promise for improving food security, and livestock feed in small-scale farming systems in Africa. However, its seeds contain anti-nutritional factors (ANFs), primarily L-Dopa, which must be reduced to safe levels before human or animal consumption. This factsheet outlines recommended seed processing methods that are practical and effective for small-scale, resource-poor farmers